In House Training (IHT): Upaya Meningkatkan Kompetensi Guru dalam Memanfaatkan Media Digital Canva - caswita caswita (Balai Diklat Keagamaan Semarang, 2024)
This research aims to improve teacher competency in learning through In House Training (IHT) in the use of Canva media. This research method uses a pre-experimental design type of one-group pre-test post-test design. The research was conducted at Syekh Tubagus Abdullah Elementary School, Purbaratu District, Tasikmalaya City. The research was conducted at the beginning of the even semester 2021/2022, in January-June 2022. The population in this research was all teachers at Syekh Tubagus Abdullah Elementary School, Purbaratu District, totaling 10 people. The results of the research show that based on the data obtained, in phase I as many as 9 teachers at Syekh Tubagus Abdullah Elementary School were able to master the material for making Canva learning videos well. Only one teacher scored below average. Based on the results of phase 1, it is necessary to carry out phase II IHT activities again. Meanwhile, in phase II, the results of the implementation of In House Training were based on instruments that had been filled in by 10 respondents or participants (Teachers) and had achieved an average score of 100, this means that most of the indicators based on previous provisions could be achieved very well. Based on existing data, the conclusion is that IHT activities have succeeded in increasing teacher competence in utilizing animated videos in learning activities.